Benign synthesis of quinolinecarboxamide ligands, H2bqbenzo and H2bqb and their Pd(II) complexes: X-ray crystal structure, electrochemical and antibacterial studies. Issue 14 (18th July 2017) - Meghdadi, Soraia; Amirnasr, Mehdi; Kiani, Mahsa; Fadaei Tirani, Farzaneh; Bagheri, Maryam; Schenk, Kurt Job
Abstract: Two carboxamide ligands, H2 bqbenzo 3, 4-bis(2-quinolinecarboxamido)benzophenone and H2 bqb N, N′ -bis[(2-quinolinecarboxamide)-1, 2-benzene], have been prepared using tetrabutylammonium bromide as an environmentally benign reaction medium. Two new Pd(II) complexes, [Pd II (bqbenzo)] (1 ) and [Pd II (bqb)] (2 ), have been synthesized, characterized, and their structures determined by single crystal X-ray diffraction. The di-anionic ligands, bqbenzo 2− and bqb 2−, are coordinated via two Namide atoms and the nitrogens of the two quinoline rings, with Pd−Namide < Pd–Nquinoline bond lengths. The geometry around palladium(II) in both complexes is distorted square planar. The electrochemical behaviors of the ligands and their Pd(II) complexes have been investigated by cyclic voltammetry in DMF. An irreversible Pd II/I reduction is observed at −1.06 V for1 and at −1.177 V for2, indicating the influence of the R substituent on the central phenyl ring of carboxamide ligands on the Pd II/I reduction potential. The ligands and palladium complexes were also screened for in vitro antibacterial activity. The Pd(II) complexes show strong biological activity against S.typhi and E.coli as Gram −ve and B.cereus and S.aureus as Gram +ve bacteria comparable to the antibiotic penicillin. The antibacterial results also reveal that coordination of Pd(II) significantly improves the activity. Abstract :